(3GdPNjQI aj eMGSf Cgd GdLRjQIs - (3Ydj Hf HSGe GdTfJQjfj GdCfOdSj, CHh GdMSf,J (B542 (3g` s
(3ChdgG (B:s
(3GdbSe GdKGdK ef cJGH GdPNjQI ai eMGSf Cgd GdLRjQI PcQ GdLGfH GdTQbi ef LRjQI GdCfOdS hJSejI ef fLe s
(3BNQgG (B:s
(3hEf CMQe bVGA GdYOd CQLY (B: (3Edi cfajf ef gLQ hUHQ GfJgi GdbSe GdQGHY ef cJGH GdPNjQI hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B43s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs